Performance of alkaline reactive materials in the remediation of acidic groundwater - Alexandra N. Golab Buddhima Indraratna Mark A. Peterson (Chinese journal of geochemistry, 2006)
Acidic groundwater and surface water are common problems in coastal Australia causing massive fish kills, attack of concrete and steel structures, and clogging of waterways. The best solution is the construction of a permeable reactive barrier （PRB） to neutralise the acidic groundwater before entering nearby waterways. A PRB consists of a trench filled with reactive material that intersects the flow-path of a contaminant plume and ameliorates the contaminated groundwater. A PRB is being designed in a pilot scale study in ASS in southeastern Australia. The groundwater is acidic （pH 3） with high A1 （40 mg/L） and Fe （530 mg/L） levels. When the acidic groundwater comes into contact with this PRB, the acid will be neutralized by the alkaline reactive materials and the aluminum and iron will be removed from the groundwater. Twenty-five alkaline materials were tested for use in the PRB, with an emphasis on waste materials, including oyster shells and recycled concrete. Batch tests were used to select the best two reactive materials for use in the column tests. The pH achieved by each material was controlled by the reaction kinetics of the dominant alkaline component.